The synthesis and antimicrobial activity of some new methyl N-arylthiocarbamates, dimethyl N-aryldithiocarbonimidates and 2-arylamino-2-imidazolines - Servi, S; Genc, M; Gür, S; Koca, M (Elsevier France-Editions Scientifiques Medicales Elsevier, 2005)
Methyl N-arylthiocarbamates (2a-d) and dimethyl N-aryldithiocarbonimidates (2e-i) were synthesized from the reaction of aromatic amines with carbon disulfide and methyl iodide and NaOH in various quantitative amounts. 2-Arylamino-2-imidazolines (3a-i) were prepared by heating both methyl N-arylthiocarbamates (2a-d) and dimethyl N-aryldithiocarbonimidates (2e-i) with 1,2-diaminoethane under reflux. o-chlorobenzyl derivatives of [1,3,4]-thiadiazole-2-yl substituted aminoimidazoline compounds were synthesized by treatment of [1,3,4]-thiadiazole-2-yl substituted aminoimidazolines (3h-i) with 2-benzyl chloride in basic medium and DMSO. Some of the synthesized compounds were tested in vitro for their antimicrobial activity. All of the selected compounds showed some antimicrobial activity against test microorganisms. Compounds 2f and 3f which have 1,3-benzothiazol ring exhibited a weak activity against Candida globrata. [GRAPHICS] (c) 2005 Elsevier SAS. All rights reserved.
Keywords: antimicrobial activity; methyl N-arylthiocarbamates; dimethyl N-aryldithiocarbonimidates; 2-arylamino-2-imidazolines